ROLE OF LAND DEED OFFICIALS IN LEGAL SATISFACTION GUARANTEE FOR COMPLETE SYSTEMATIC LAND REGISTRATION - Ayu Citra Santyaningtyas; Rico Zubaidi (NOTARIIL Jurnal Kenotariatan, 2020)
Complete Systematic Land Registration (PTSL) as an accelerated land registration program in Indonesia led directly by the President needs to provide assurance and legal protection of ownership of land rights. PTSL in this case is assigned to the Adjudication Committee which functions as the executor of PTSL according to the Regulation of the Minister of Agrarian/Head of the National Land Agency. PPAT as a public official mandated by Government Regulation Number 24 of 1997 concerning Land Registration in fact could not be found its role in the implementation of PTSL both outside and within the Adjudication Committee. This study aims to examine the role of PPAT that exists and should be present in the implementation of PTSL. The research methodology used is normative legal research with literature study in primary and secondary data collection. The results of the study found no role for PPAT in PTSL legislation. If referring to Government Regulation No. 24/1997, all transitions after the birth of this regulation require a PPAT deed as written evidence of ownership or transfer of land rights. The Adjudication Committee as the executor of PTSL should coordinate with PPAT to ensure that PTSL meets the legal data research stage so that an orderly, complete registration of land is achieved and provides legal certainty of ownership of land rights.